Analisis Pelaksanaan Pelatihan Jarak Jauh Teknis Substantif Model-model Pembelajaran di Balai Diklat Keagamaan Denpasar - I Wayan Arya Adnyana (Jurnal Pendidikan Agama, 2021)
The purpose of this study was to analyze the Implementation of Substantive Technical Distance Learning for Learning Models at the Denpasar Religious Education and Training Center. Distance learning is open education with a relatively tight structured learning program and a learning pattern that takes place without face-to-face or separation between the training participants. The method used in this research is descriptive qualitative with the main data collection techniques are observation, interviews and documentation study. The focus of research in this study is the analysis of the implementation of Substantive Technical Distance Learning Models. Implementation of Substantive Technical Distance Learning Models at BDK Denpasar consists of three things including planning, implementation, and evaluation. In planning the things that are done is to formulate good goals from the point of view of the skills or activities that are expected to be achieved after the distance learning finish. In addition, planning has been carried out as well as possible, marked by holding technical guidance on distance learning and a preparatory meeting to equalize perceptions about the page and how to fill in the content. The implementation of distance learning has gone well in accordance with the plan, but the presence of signal problems or stagnant internet did not reduce the enthusiasm and motivation. While the evaluation consists of giving assignments, discussion forums, examinations. So that the three aspects both attitudes, knowledge and skills assessment can be fulfilled.